Analisis Normalisasi Sistem Drainase dan Penerapan Metode Lid pada Kelurahan Tegal Gede, Kabupaten Jember - Renan Amru Kafi (Fakultas Teknik, 2025)
The way land is being used in Tegal Gede, Jember Regency, is having a profound impact on its existing drainage system. This isn't surprising, given the rapid urban expansion and infrastructure development that have dramatically reshaped land use patterns in recent years. These changes are particularly noticeable and problematic in areas already prone to waterlogging and flooding The EPA Stormwater Management Model (SWMM) software is being used for hydrological modeling to gain a much deeper understanding of how changes in land use are affecting water runoff. The results from this analysis will clearly show how runoff behaves with conventional drainage systems, when Low Impact Development (LID), and normalization drainage concepts are applied. To ensure the accuracy of these findings, the research will validate the SWMM's water level simulations by comparing them directly with real-world observations from field conditions in Tegal Gede, Jember. Research in Tegal Gede Subdistrict reveals that alterations in land use have considerably influenced runoff. While the Low Impact Development (LID) concept was implemented, it hasn't fully solved the problem of waterlogging during heavy rainfall. This analysis provides key insights into the ongoing difficulties and future possibilities for drainage management in areas experiencing significant land use changes.
Approved by Teddy
Keywords: Low Impact Development (LID); drainage normalization; drainage system; EPA Stormwater Management Model (SWMM); Runoff response